Safety and long-term efficacy of AAV1.SERCA2a using nebulizer delivery in a pig model of pulmonary hypertension. (September 2018) - Watanabe, Shin; Ishikawa, Kiyotake; Plataki, Maria; Bikou, Olympia; Kohlbrenner, Erik; Aguero, Jaume; Hadri, Lahouaria; Zarragoikoetxea, Iratxe; Fish, Kenneth; Leopold, Jane A.; Hajjar, Roger J.
Nebulization delivery of adeno-associated virus serotype 1 encoding sarcoplasmic reticulum Ca 2+ -ATPase2a (AAV1.SERCA2a) gene was examined in a Yukatan miniature swine model of chronic pulmonary hypertension (n = 13). Nebulization of AAV1.SERCA2a resulted in homogenous distribution of vectors, lower pulmonary vascular resistance, and a trend towards better long-term survival compared to control animals.